2022
DOI: 10.1002/cpe.7423
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to alleviate data sparsity and generate dynamic fruit recommendations from point‐of‐sale data

Abstract: Summary Recommender systems have become a core part of the retail experience. Retailers often rely on recommender systems to help them drive more conversions through targeted communication and advertisements. However, recommender systems are not one size fits all. Specialized retailers require specialized recommender systems to consider various features, attributes, and dynamics about the product category. In this paper, we have proposed a novel fruit recommender system that generates dynamic recommendations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This process, known as social listening, offers valuable insights into customer needs, expectations, and emerging trends. By understanding public perception, companies can make informed decisions, address concerns, and identify areas for improvement 39,54 …”
Section: Discussion and Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…This process, known as social listening, offers valuable insights into customer needs, expectations, and emerging trends. By understanding public perception, companies can make informed decisions, address concerns, and identify areas for improvement 39,54 …”
Section: Discussion and Comparisonmentioning
confidence: 99%
“…By understanding public perception, companies can make informed decisions, address concerns, and identify areas for improvement. 39,54 Influencer marketing: Big data assists in identifying important persons on social media who have a substantial influence on their followers' thoughts and purchase decisions. Companies can find influencers aligned with their brand and target audience through data analysis.…”
Section: Affordable Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xiao Qian, a scholar, designed a recommendation algorithm and finally realized a mixed recommendation system for fruit matching based on user behavior characteristics, and the results showed that it could effectively improve the quality of fruit matching recommendation [5] . Gupta Garima, a foreign scholar, proposed a fruit recommendation system using a deep learning approach that takes into account the temporal dynamics of the fruit market, such as price fluctuations, fruit seasonality and quality changes that occur throughout the year, in order to improve the sales of retailers [6] . A synthesis of the literature shows that none of the existing studies have proposed fruit recommendations based on nutritional composition for specific populations.…”
Section: Introductionmentioning
confidence: 99%